Implementasi Metode Praktikum Berbasis Inquiry Untuk Meningkatkan Hasil Belajar IPA Pada Materi Perpindahan Kalor - Rozaqti, Herlina; Trisnawati, Oky Ristya (IAINU Kebumen, 2024)
The objectives of the study are: (1) to determine the application of inquiry-based practicum method to the learning outcomes of science of heat transfer material in grade V B students at MI Ma'arif NU Karangsari Kebumen; (2) to determine the influence of the inquiry-based practicum method on the learning outcomes of science heat transfer material in grade V B students at MI Ma'arif NU Karangsari Kebumen. The type of research used in this study is Control Group Pretest-Posttest Design. This design uses two measurements of students' understanding of the heat transfer material to be sampled. The first measurement of the pretest was carried out to find out the understanding of students before being given the treatment of the application of the inquiry-based practicum method. The second posttest is the provision of tests to students to find out students' understanding after applying the inquiry-based practicum method. The subjects in this study are students of class V A and B MI Ma'arif NU Karangsari Kebumen as many as 37 students.The results of this study show that there is an application of the inquiry-based practicum method carried out in six steps, namely: presenting the problem, developing a hypothesis, designing an experiment, conducting an experiment, analyzing data and making conclusions. Then the influence of the inquiry-based practicum method is evidenced by the results of the hypothesis test which obtained a sig value of 0.001 where the value is in accordance with the Ho rejection criteria. So it can be concluded that Ho was rejected and Ha was accepted where Ha reads